HANDRYER OTOMATIS DENGAN SENSOR TINGKAT KELEMBAPAN UNTUK MENGOPTIMALKAN PENGERINGAN TANGAN - Falanta, Joerda; Sulaiman, Sulaiman; Ariandi, Muhammad; Dasmen, Muhammad Novrianda (Fakultas Teknik Universitas Muhammadiyah Sumatera Barat, 2025)
Conventional hand dryers often rely on manual buttons or simple infrared sensors, which can pose risks of germ transmission and limitations in responsiveness and detection accuracy. This paper proposes an innovative solution by integrating Internet of Things (IoT) technology to develop an automated hand dryer connected online using an ESP32 microcontroller. IoT technology enables remote control and real-time monitoring, enhancing cleanliness and health by reducing direct contact with the device's surface. The study includes testing proximity sensors, thermocouples, and moisture sensors to ensure optimal performance. Proximity sensors demonstrate good responsiveness within 0-5 cm, thermocouples effectively manage temperature, and moisture sensors provide appropriate audio feedback based on hand moisture conditions. The findings indicate that the IoT-integrated automated hand dryer not only improves usage efficiency but also significantly contributes to public hygiene and health, offering potential innovation in sanitation technology.Keywords: Automated Hand Dryer, Internet of Things (IoT), ESP32 Microcontroller, Proximity Sensor, Thermocouple Sensor, Moisture Sensor